Introducing a diploma course at the Department of Visual Arts at Stellenbosch University: an investigation into attitudes and perceptions regarding social and racial transformation - Conradie, Stephane Edith (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.